ANALISA UNJUK KERJA AKUMULATOR DAN BIAYA PADA ALAT PENYIRAM TANAMAN BAWANG MERAH - Fadwah Maghfurah; Windarta Windarta; Andis Munandar (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2018)
One of the latest innovations for watering plants onion is using DC water pump machine with a power source, Accumulators, charger, and material selection right framework to fit the plan and adjust first hand, the pump can emit large amounts of water and can spread to all parts of the plot width onion plants and minimize the operational expand, as well as cheap, as well as effective to raise profit, as the power  Accumulator sufficient to flushing. Accumulators used had amounted to 10 Ah Ampere hour to run the pump with a power of 60 watts for 1.6 hours (96 minutes). Moment of force equilibrium this tool on RAV = 34.549 N and RVB = 35.109 N. Break Even Point (BEP) for sprinklers rupiah onion crop is RP 1.641 million. In the area there are 36 plots that would require 18 times watering, then 105 x 18 = 1890 seconds (31 minutes 30 seconds).